An overview of educational inequality in India: The role of social and demographic factors - Garg, Mausam Kumar; Chowdhury, Poulomi; SK, Md Illias Kanchan (Frontiers in Education, 2022)
India has made significant progress over the time in abating illiteracy and improving primary level of education. However, socio-economic inequality with regards to education still persists. Using the latest rounds of National Sample Survey Organization, it is observed that the inequality has gone down between 2007 and 2018, but the Gini indices are still concentrated around 38%. Decomposition of Gini and Shapley regression approach indicates that the within group component and rural-urban division contributes the most in educational inequality. Tobit regression model signifies that digital exposure, household occupation, wealth quintile and household size play a key role in determining educational attainment. The paper underscores the improvement of education in rural areas by focusing on school infrastructure, e-learning, educational quality, and parent’s involvement.